2013
DOI: 10.1093/jxb/ert399
|View full text |Cite
|
Sign up to set email alerts
|

The heat shock factor family fromTriticum aestivumin response to heat and other major abiotic stresses and their role in regulation of heat shock protein genes

Abstract: Heat shock factors (Hsfs) play a central regulatory role in acquired thermotolerance. To understand the role of the major molecular players in wheat adaptation to heat stress, the Hsf family was investigated in Triticum aestivum. Bioinformatic and phylogenetic analyses identified 56 TaHsf members, which are classified into A, B, and C classes. Many TaHsfs were constitutively expressed. Subclass A6 members were predominantly expressed in the endosperm under non-stress conditions. Upon heat stress, the transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
228
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(250 citation statements)
references
References 77 publications
8
228
1
Order By: Relevance
“…3). A similar situation was found in other plants, like Arabidopsis (A1-type Hsfs ) [55], apple ( MdHsfA1a , A1d , B1a and B1b ) [50], wheat ( A1 and A8 groups, and some A2 and A6 group members) [41]. The tissue- and stage-specific expression patterns of pepper CaHsf family genes, such as CaHsfA1b in root, CaHsfB3a in PL-16DPA, CaHsfB5 in PC-B10, and CaHsfC1 in leaf and PL-B5, indicated that CaHsfs might be widely involved in the development of various organs and tissues, which is helpful to further understanding the functions of CaHsf genes in pepper developmental biology [56].…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…3). A similar situation was found in other plants, like Arabidopsis (A1-type Hsfs ) [55], apple ( MdHsfA1a , A1d , B1a and B1b ) [50], wheat ( A1 and A8 groups, and some A2 and A6 group members) [41]. The tissue- and stage-specific expression patterns of pepper CaHsf family genes, such as CaHsfA1b in root, CaHsfB3a in PL-16DPA, CaHsfB5 in PC-B10, and CaHsfC1 in leaf and PL-B5, indicated that CaHsfs might be widely involved in the development of various organs and tissues, which is helpful to further understanding the functions of CaHsf genes in pepper developmental biology [56].…”
Section: Discussionsupporting
confidence: 72%
“…Notably, five out of seven members of class CaHsfB, especially B1 and B5, were significantly up-regulated by HS in R9 leaves, which was in accord with the HsfB1 and B2 groups in wheat [41]. Most HsfBs, except HsfB5, contain the tetrapeptide LFGV in the C-terminal domain, which is assumed to function as a repressor motif in the transcriptional machinery [8].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Genes involved in these mechanisms contain HSE motifs that bind heat shock factors (HSFs), and are up-regulated during heat stress. HSE have been found to be consistently conserved in the regulatory regions of many heat induced genes [30]. The presence of a HSE motif in the 1.0 kbp regulatory regions of all rice Asc-Glu genes may imply the ability of the genes to survive high temperature stress condition or the participation or need during high temperature stress condition and ensure protection of cellular homeostasis.…”
Section: Stress Response Associated Cis-elementsmentioning
confidence: 99%
“…One of the most important thermotolerance mechanisms in plants is the induction of heat shock proteins (Hsps), which typically act as molecular chaperones to reduce damage to cells (Wang et al, 2004;Xue et al, 2014). Based on their molecular weights, plant Hsps are divided into 5 groups, including Hsp100, Hsp90, Hsp70, Hsp60, and the small Hsp (sHsp) family (Wang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%